1990
DOI: 10.1021/ja00158a001
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state racemization kinetics and chiroptical activity of a labile metal complex in aqueous solution. Time-resolved circularly polarized luminescence study of tris(dipicolinato)europate (3-) in water and deuterium oxide

Abstract: Time-resolved circularly polarized luminescence (TR-CPL) measurements are used to characterize the excited-state chiroptical activity and racemization kinetics of Eu(dpa)33~(dpa = dipicolinate) in H20 and D20 solutions at temperatures between 293 and 353 K. Racemic Eu(dpa)33~i s excited with circularly polarized light to create an enantiomeric excess of one optical (configurational) isomer in an excited electronic state, and then comparisons between time-resolved total luminescence and circularly polarized lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…[1] and [3] . Examining each as the triflate salt in acetonitrile solution (or water), the greater the degree of conformational rigidity in the complex, the higher was the measured g em value Table 1.…”
Section: Conformational Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…[1] and [3] . Examining each as the triflate salt in acetonitrile solution (or water), the greater the degree of conformational rigidity in the complex, the higher was the measured g em value Table 1.…”
Section: Conformational Exchangementioning
confidence: 99%
“…1 To some extent this lack of knowledge has inhibited the development of emissive lanthanide complexes as structural or reactive probes to signal the nature of the local ionic or chiral environment. The reason why our understanding remains very limited, notwithstanding the promulgation of robust theories relating local lanthanide symmetry to the electronic and chiroptical features associated with f-f transitions, 2À4 is linked directly to the absence of well-defined complexes whose structure and solution exchange dynamics have been studied in detail.…”
mentioning
confidence: 99%
“…However, it should be noted that whilst this method has been demonstrated successfully with ligands such as L 12 , recent studies involving complexes of this ligand have reported the presence of two species in solution. [89][90][91] NMR experiments have shown that these species may be thought of as regioisomers, with their existence being attributed to the fact that it is possible for the ring substituent to be located in one of two nonequivalent positions (Figure 1.20).…”
mentioning
confidence: 99%
“…It is important to highlight that a number of metalloproteins and vitamin B 12 derivatives have also been found to be capable of inducing a CPL signal from [Ln(DPA) 3 ] 3-in solution via this mechanism. [122][123][124] In the case of the corrinoid vitamin B 12 and its derivatives, the observation of an enantioselective quenching effect has been attributed to energy transfer in a hydrogen-bonded encounter complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation